Images recognition by template matching depended on correlation coefficient - hadeya Salih Abdullah (College of Education for Pure Sciences, 2010)
Abstract In this research it has been using template matching to images recognition, after saving some templates for images as like geometrical shapes English characters and numbers and then input the template which is to be recognized after normalizing it to template size if not equal size templates saved inside machine to recognizing pixel by pixel for binary and gray images. This method given good results, as well used template matching depend on correlation to recognition and this method has given best and strong recognizing.